JN.1: enhanced immune evasion ability propels it to become the predominant strain in China, unlikely to trigger pandemic similar to late 2022 - Du, Peng; Li, Meiyi; Wei, Guohui; Guo, Chengbin; Li, Ning (Frontiers in Public Health, 2024)
We tracked the immune landscape in the population after the SARS-CoV-2 pandemic in late 2022 in China. Our findings suggested that low levels of neutralizing antibodies against BA.5 subbranches before the pandemic might have contributed to the national outbreak at the end of 2022. The widespread breakthrough infections subsequently increased immunity to BA.5, XBB.1.5/1.9.1, and JN.1, inhibiting a new wave of large-scale infections caused by XBB subbranches in China. Additionally, JN.1 demonstrated enhanced immune evasion capabilities; however, Chinese residents had comparable levels of neutralizing antibodies against JN.1 as those observed for XBB.1.5 among confirmed cases at the end of 2022.Therefore, we anticipate that JN.1 will replace XBB subbranches as the predominant epidemic variant in subsequent transmissions within China. However, it is unlikely to cause a large-scale spread comparable to that witnessed at the end of 2022, with transmission patterns potentially resembling those observed for XBB post-pandemic.